2018
DOI: 10.1002/jcb.27786
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Downregulation of microRNA‐1469 promotes the development of breast cancer via targeting HOXA1 and activating PTEN/PI3K/AKT and Wnt/β‐catenin pathways

Abstract: Breast cancer (BC) is a common malignancy which is the most frequently diagnosed cancer in women all over the worldwide. This study aimed to investigate the roles of miR‐1469 in the development of BC, as well as its regulatory mechanism. The expression levels of miR‐1469 in BC tissues, serum, and cell lines were determined. Effects of overexpression of miR‐1469 on MCF7 cell viability, colony‐forming ability, apoptosis, migration, and invasion were then investigated. Furthermore, the potential target of miR‐146… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…cancers. Consistently, low expression levels of microRNAs targeting HOXA1 are also associated with poor prognosis and Tamoxifen resistance (3,(62)(63)(64)(65)(66). Therefore, early de novo HOXA1 expression in the mammary gland might lead to the development of aggressive subtypes of breast cancer, and late HOXA1 expression in an ER+ tumor environment might lead to endocrine therapy resistance.…”
Section: Discussionmentioning
confidence: 98%
“…cancers. Consistently, low expression levels of microRNAs targeting HOXA1 are also associated with poor prognosis and Tamoxifen resistance (3,(62)(63)(64)(65)(66). Therefore, early de novo HOXA1 expression in the mammary gland might lead to the development of aggressive subtypes of breast cancer, and late HOXA1 expression in an ER+ tumor environment might lead to endocrine therapy resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, we tested HOXA1 and verified it as a direct target of miR-10b. As one of the HOX family members, HOXA1 is involved in various biological processes, including cell apoptosis and growth (Zhang et al, 2018). For instance, it was demonstrated that HOXA1 can inhibit the migration, invasion and growth of HepG2 cells (Zha et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that p53 can up-regulate the expression of miR-29c in colon carcinoma cells, and miR-29c can act on its downstream target gene PHLDB2 to down-regulate its expression, thereby inhibiting the invasion and metastasis of colon carcinoma cells. By contrast, the binding site of p53 and miR-17-92 promoter region covers the TATA box region, thus interfering with the binding of TATA box binding protein (TBP) with TATA box, thereby inhibiting the transcription of miR-17-92 and down-regulating its expression level (Zhang et al, 2018a;Zhang et al, 2018b;Zhang et al,2018c).…”
Section: Discussionmentioning
confidence: 99%